THE INFLUENCE OF FEAR OF MISSING OUT (FOMO) ON IMPULSE BUYING WITH PRODUCT UNIQUENESS AS A MODERATING VARIABLE - Dewi Maharani; Saida Zainurossalamia ZA; Asnawati Asnawati; Johni Eka Putra; Eva Desembrianita (JURNAL ILMIAH EDUNOMIKA, 2024)
ABSTRACT This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as the main foundation to strengthen the new arguments that the researcher has designed. The previous research referred to in this article is . The data used in this research is primary data that researchers obtained from Tiktokshop, Shopee and Marketplace consumers. The data used in this research was analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Fear of Missing Out variable can have a positive relationship and a significant influence on Impulsive Buying Decisions because the P-Values value is positive and is below the 0.05 significance level, namely 0.006 . This can be caused by the greater the Fear of Missing Out, consumers are more targeted, want to follow trends, and make impulsive purchasing decisions. In the next line, which is also a different formulation from the two studies above, is the Product Uniqueness variable which is believed to moderate the influence of the Fear of Missing Out variable on Impulsive Buying Decisions. This can be proven because the P-Values value is positive and is below the 0.05 significance level, namely 0.000, more significant than the direct test of 0.006. These results indicate that curiosity, desire to buy, and the feeling of not wanting to miss the trend will increase if FOMO is accompanied by a unique product that attracts consumers. Thus the first and second hypotheses in this research can be accepted. Keywords: Fear of Missing Out, Impulse Buying, Product Uniequeness